PREDICTION TINGKAT POTENSI PEMBELI PADA HARI SPECIAL DI TOKO MITRA SHOPEE - Artisya, Nur; Saut Pintubipar Saragih (LPPM Universitas Putera Batam, 2022)
Shopee is a Marketplace Platform that stepped on the Indonesian market at the peak of May 2015 and started running at the end of June 2015 in Indonesia. An item is whatever can be proposed to a market to fulfill a need or need, including actual merchandise, administrations, encounters, occasions, individuals, places, properties, associations, data and thoughts. The shopee partner of the Bagan Wholesale store has been established for 3 years with a total of more than 700 products, selling household goods, fashion, decorations etc. Implementing Data Mining, especially classification using the C4.5 algorithm in predicting buyers at Bagan Wholesale shopee partner stores. The choice tree strategy is a flowchart structure that is like a tree structure, each tree point is a quality that has been tried, each branch is an experimental outcome, and the end point is the subsequent class division. In the analysis process, the researcher uses data mining techniques using the C4.5 classification algorithm which is processed using the Rapidminer application version 9.10.001 in order to find buyer predictions at shopee partner stores.